Pemberdayaan Ibu Rumah Tangga Kelurahan Air Putih Melalui Pembuatan Eco-Enzyme dari Sampah Organik sebagai Sabun Cair - Deviona, Deviona; Chairul, Chairul; Armaini, Armaini; Yusnimar, Yusnimar; Arofi, Habib; Putri, Alivia Hardana; Tasman, Annaya Qamara; Darliansyah, Danny; Indriana, Hanifah; Sayyidhani, Muhammad Hisna; Hasibuan, Muhammad Ilham Febrian Mahodum; Apriliani, Prapita; Emelda, Retta; Wulandari, Siti Rahmi Indri (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
Lack of education in waste management has led to a large amount of waste being dumped in landfills. Organic waste is the largest type of waste disposed of in landfills. If organic waste is not managed properly, it can cause unpleasant odors in the environment and become a risk factor for global warming and explosions in landfills. Until now, waste management, both organic and inorganic waste, is still a challenge. This is also the case in RW 02 Kelurahan Air Putih. The community directly disposes of household waste without sorting the waste by type. In addition, the community also does not know how to process organic waste into useful items such as eco-enzyme and eco-enzyme processed products, namely cleaning fluids. This community service activity aims to increase community knowledge and skills on how to process household organic waste into eco-enzyme and liquid soap made from eco-enzyme. The targets in this activity are housewives in RT 06, RT 07, and RT 08, RW 02 Air Putih Village. The method used in this community service activity is socialization and training on how to make eco-enzyme and multipurpose liquid soap. The results obtained from this activity are the increased knowledge and skills of the community in processing organic waste into eco-enzyme and multipurpose liquid soap. The community is also enthusiastic and interested in making these products again in their homes.